Principal's Managerial Performance to Improve Quality of Education at Vocational High School - Sutikno, Sutikno (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
This study discusses the importance of principal management in efforts to improve the quality of education in vocational high schools, given the importance of the role of school principals where all policies are oriented towards improving the quality of education. Based on these objectives, a research design was then chosen using a quantitative design. The subject used in this study consisted of three groups, namely vice principals, education staff, and students. The instrument used was a questionnaire used to measure the managerial skills of school principals which consisted of three aspects including the innovator aspect consisting of four indicators, the motivator consisting of seven indicators, and the supervisor consisting of three indicators. The empirical methodology used in practical descriptive analysis represents trends and variations in data such as mean, median, and mode), which are very useful for explaining research data. Descriptive statistical analysis assisted by the SPSS program. The results of the study found that school principals had been able to improve the quality of education in vocational schools based on the innovator aspect with the highest average of 29.40 (Std. Dev 20.28), motivators with the highest average of 49.00 (Std. Dev 38.33), and supervisors with the highest average of 49.00 (Std. Dev 37.59).